X-ray absorptiometry for non-destructive monitoring of the salt uptake in bone-in raw hams during salting. (January 2015) - Fulladosa, E.; Muñoz, I.; Serra, X.; Arnau, J.; Gou, P.
Abstract: Salt uptake variability in dry-cured ham batches is a problem for the dry-cured ham industry because part of the hams have either an excess or a lack of salt and therefore are more prone to sensory defects. The aim of this study was to evaluate the feasibility of an X-ray inspector for a non-destructive, on line determination of the salt uptake in entire bone-in hams during the salting procedure. Moreover, its usefulness in combination with a modified salting procedure to reduce the salt content and within batch variability was evaluated in an industrial case study. Predictive models for salt content, accurate enough for classification purposes (RMSEV = 0.210−0.257%), were developed using only one X-ray energy (50 kV). The use of an X-ray inspector in combination with slight modifications of the process allowed the reduction of the average salt content a 13.75% and 26.67% and a within-batch standard deviation from 0.45% to 0.21% or 0.26% depending on the reduced target salt content. Highlights: X-ray inspectors can predict salt uptake of hams during the salting process. Only one incident energy is needed to predict accurately enough salt content in hams. Salt, water and fat contents of the hams do not affect salt content prediction error. Salt uptake variability can be reduced by adapting the salting process. Salting process is adapted according to the predicted salt content by X-ray.